Water-based adhesive and preparation method thereof

CN119614129APending Publication Date: 2025-03-14FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411515181.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The seamless glue bonding process has glue spilling problems during the fine construction process, which affects the aesthetics of composite fabrics.

Method used

The aqueous polyurethane adhesive with a double-size particle size structure is used to control the particle size distribution and component ratio of the adhesive through elastic component A of large-size particle size and adhesive component B of small-size particle size, combined with other additive component C, to achieve the effect of small amount of hot press deformation, small amount of overflow and high bond strength.

Benefits of technology

This technical solution effectively reduces the amount of glue overflow of adhesive under high temperature and high pressure conditions, improves the bonding strength, is suitable for high temperature and high pressure composite construction technology, and supports precision and patterning construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614129A_ABST
    Figure CN119614129A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based adhesive and a preparation method thereof, and belongs to the technical field of high polymer materials. The water-based adhesive comprises the following components: an elastic component A with a large-scale particle size; a viscous component B having a small particle size; the water-based adhesive is a water-based polyurethane adhesive with double-scale particle size components, the elastic component A with the large-scale particle size is a key component with small glue overflow amount of the adhesive under high-temperature and high-pressure construction conditions, and the viscous component B with the small-scale particle size ensures the bonding strength of the adhesive. The water-based adhesive prepared by the invention has the advantages of small hot-pressing deformation, small excessive glue amount, high bonding strength and the like, effectively solves the problems of excessive glue and the like in a refined construction process in a seamless glue laminating process, can be subjected to precise and patterned construction through printing, and is suitable for a high-temperature and high-pressure composite construction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a water-based adhesive and a preparation method thereof, belonging to the technical field of polymer materials. Background Art

[0002] Seamless lamination is a process that uses bonding instead of sewing to produce seamless composite fabrics. This process is mainly used in the clothing and shoemaking industries.

[0003] At present, the most common seamless bonding processes on the market are mainly the following: 1) Glue-free bonding, which uses the heat generated by high-frequency vibration waves to directly melt and bond the hot-melt fabric. This method is simple to operate, but the materials are limited to chemical fiber fabrics that can melt by themselves, such as polyester fabrics, polypropylene fabrics, nylon fabrics, etc.; 2) Film bonding, which is to make the hot melt adhesive into a film, which not only ensures the uniformity of bonding, but also has a soft feel. At the same time, it can be finely operated without defects such as overflowing glue. 3) Glue bonding, mainly using solvent glue, water-based glue, and wet-curing glue to bond fabrics. This method has high bonding strength, but it is easy to produce local overflowing glue during high-temperature and high-pressure processing, affecting the overall aesthetics of the composite fabric. For example, the patent with publication number CN110396290A discloses a hot-melt powder modified water-based polyurethane resin and its preparation method, in which the polyurethane resin is compounded with a closed curing agent and dried at low temperature to obtain a film. The adhesive film is heat-pressed to obtain a composite fabric, which greatly improves the water-washing fastness of the composite fabric; the patent with publication number CN112143440A discloses a polyurethane adhesive for seamless down jackets. The technical means such as combining water-based polyurethane with polyether polyol as the main body and modified nano-silica solve the defects of the existing polyurethane adhesive for seamless down jackets, such as lack of air permeability and poor hydrolysis resistance.

[0004] Most seamless lamination products are mainly made by glue-free lamination and film lamination. The convenience of glue lamination is not as good as that of film lamination. Therefore, glue lamination is mainly used for the lamination of large-area fabrics. Although glue lamination still has problems such as glue overflow in fine construction, it has the advantage of bonding strength and still has great application prospects in the future. Summary of the invention

[0005] In order to solve the problem of glue overflow during the refined construction process in the existing technology of seamless glue bonding process, the present application provides a technical solution of a water-based polyurethane adhesive with a dual-scale particle size structure, which utilizes an elastic component A with a large particle size (referred to as: elastic component A); a viscous component B with a small particle size (referred to as: viscous component B) to achieve the advantages of water-based polyurethane adhesive such as small hot pressing deformation, small glue overflow, and high bonding strength. It can also be precisely and patterned through printing for construction, and is suitable for high temperature and high pressure composite construction processes.

[0006] This application adopts the following technical solutions:

[0007] According to one aspect of the present application, a water-based adhesive is provided, comprising the following components:

[0008] Elastic component A with large particle size;

[0009] A sticky component B with small particle size;

[0010] Other auxiliary components C.

[0011] In the present application, the function of the elastic component A with large particle size is to be a key component of the water-based adhesive with small deformation and overflow under high temperature and high pressure conditions; the function of the viscous component B with small particle size is to ensure the bonding strength of the adhesive; the function of the other auxiliary component C is to defoam, level, thicken, etc.

[0012] Optionally, the particle size distribution range of the elastic component A is 0.01-100 μm;

[0013] The particle size distribution range of the viscous component B is 0-1.0 μm.

[0014] Optionally, the particle size distribution range of the elastic component A is preferably 0.01-10 μm;

[0015] Optionally, the particle size distribution range of the viscous component B is preferably 0.01-1.0 μm.

[0016] Optionally, the components of the water-based adhesive include, by weight percentage:

[0017] Large-scale particle size elastic component A 10-88%;

[0018] Small particle size sticky component B10-88%;

[0019] Other auxiliary component C 0-2%. The lower limit of the content of other component C is not 0.

[0020] Optionally, the elastic component A is made of raw materials including the following component contents by weight percentage:

[0021]

[0022]

[0023] Preferably, the viscous component B is made of raw materials including the following component contents by weight percentage:

[0024]

[0025] Optionally, the polyamine chain extender is selected from at least one of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.

[0026] In the present application, the polyamine is used as a chain extender, which is beneficial to the formation of large-scale emulsion particles with a cross-linked structure. The elastic emulsion with a cross-linked structure can maintain its shape under heat and pressure, thereby reducing the amount of glue overflow.

[0027] Optionally, the diamine chain extender is selected from at least one of ethylenediamine, isophoronediamine, 1,6-hexanediamine, and β-hydroxyethylethylenediamine.

[0028] The reason for using diamine in the present application is that small-scale latex particles with a linear structure are formed, and the viscous latex with a linear structure can improve the bonding strength of the adhesive.

[0029] Optionally, the polyisocyanate is selected from at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and / or 4,4'-dicyclohexylmethane diisocyanate.

[0030] Optionally, the polyol is selected from at least one of polycarbonate diol, polyoxypropylene polyol, polyethylene oxide diol, polytetramethylene glycol diol, polyethylene adipate diol, polyethylene adipate diol, and polyneopentyl adipate diol.

[0031] Optionally, the weight average molecular weight of the polyol is 1000-5000.

[0032] Optionally, the hydrophilic chain extender is selected from at least one of carboxyl diol, sulfonate diamine and non-ionic chain extender.

[0033] Optionally, the carboxyl diol is selected from at least one of dimethylol propionic acid and dimethylol butyric acid.

[0034] Optionally, the sulfonate diamine is selected from sodium 2-[(2-aminoethyl)amino]ethanesulfonate.

[0035] Optionally, the nonionic chain extender is a polyethoxy ether containing a hydroxyl group or an amino group.

[0036] Optionally, the polyoxyethylene ether is polyoxyethylene monomethyl ether with 4-200 ethylene oxide units.

[0037] Optionally, the neutralizing agent is selected from at least one of triethylamine, triethanolamine, tripropylamine, ammonia water, sodium hydroxide, potassium hydroxide, and dimethylethanolamine, which can neutralize carboxyl groups.

[0038] Optionally, the other auxiliary component C comprises a defoamer, a leveling agent, and a thickener.

[0039] Optionally, the defoaming agent is selected from at least one of mineral oils, alcohols, fatty acids and fatty acid esters, amides, phosphates, silicones, polyethers, and polyether-modified polysiloxane defoaming agents.

[0040] Optionally, the leveling agent is selected from at least one of an acrylic leveling agent, a silicone leveling agent, and a fluorocarbon leveling agent.

[0041] Optionally, the thickener is selected from at least one of a cellulose thickener, a fatty alcohol or fatty acid thickener, an ether thickener, a polyacrylate thickener, and an associative polyurethane thickener.

[0042] Optionally, the ratio between the defoamer and the leveling agent is 0:10-10:0.

[0043] Optionally, the ratio between the defoamer and the thickener is 0:10-10:0.

[0044] According to another aspect of the present application, a method for preparing the above-mentioned water-based adhesive is provided, comprising the following steps:

[0045] S1, obtaining elastic component A with large particle size;

[0046] S2, obtaining a viscous component B with a small particle size;

[0047] S3, uniformly mixing the elastic component A, the viscous component B and the other auxiliary component C to obtain the water-based adhesive.

[0048] Optionally, in step S1, the preparation process of the elastic component A comprises the following steps:

[0049] S1-1, melting the polyol and removing water under vacuum;

[0050] S1-2, after step S1-1 is completed, release the vacuum in an inert atmosphere, add a hydrophilic chain extender and a polyisocyanate to the polyol in sequence, perform a prepolymerization reaction, and obtain a prepolymer;

[0051] S1-3, adding acetone to the prepolymer to adjust the viscosity, then adding water for reverse emulsification, cooling to the neutralization temperature, adding a neutralizing agent for neutralization, and obtaining a neutralized mixed solution;

[0052] S1-4, dropwise add the aqueous solution of polyamine chain extender into the neutralized mixed solution to carry out chain extension reaction, remove acetone in vacuo, and obtain elastic component A with large particle size.

[0053] Optionally, in step S2, the preparation process of the viscous component B comprises the following steps:

[0054] S2-1, melting the polyol and removing water under vacuum;

[0055] S2-2: After step S2-1 is completed, release the vacuum in an inert atmosphere, add a hydrophilic chain extender and a polyisocyanate to the polyol in sequence, perform a prepolymerization reaction, and obtain a prepolymer;

[0056] S2-3, adding acetone to the prepolymer to adjust the viscosity, then adding water for reverse emulsification, cooling to the neutralization temperature, adding a neutralizing agent for neutralization, and obtaining a neutralized mixed solution;

[0057] S2-4, dropwise add an aqueous solution of a diamine chain extender into the neutralized mixed solution to undergo a chain extension reaction, and remove the acetone in vacuo to obtain a viscous component B with a small particle size.

[0058] Optionally, the dripping rate in step S2-1 and step S2-2 is independently selected from 10-100 ml / min;

[0059] Optionally, the conditions for the chain extension reaction in step S2-1 and step S2-2 are independently selected from: reaction temperature of 25 to 50° C., and reaction time of 10 to 60 min.

[0060] Optionally, the temperature at which the polyol is melted in step S1-1 and step S2-1 is independently 90-120°C.

[0061] Optionally, the vacuum condition in step S1-1 includes: a vacuum degree of -0.01 MPa to -0.2 MPa.

[0062] Optionally, the vacuum condition in step S2-1 includes: a vacuum degree of -0.01 MPa to -0.2 MPa.

[0063] Optionally, the conditions for the prepolymerization reaction in step S1-2 and step S2-2 independently include: a reaction temperature of 50-100° C. and a reaction time of 1-10 h.

[0064] Optionally, adjusting the viscosity in step S1-3 and step S2-3 independently includes: adjusting the viscosity to 100-10000 mPa*s.

[0065] Optionally, the neutralization temperature in step S1-3 and step S2-3 is independently 25-60°C.

[0066] The beneficial effects of this application include:

[0067] The technical solution of the dual-scale particle size structure waterborne polyurethane adhesive provided in the present application is to obtain the dual-scale particle size structure waterborne polyurethane adhesive by regulating the raw material composition and the preparation method, wherein the large-scale elastic latex particles with a cross-linked structure can maintain their own shape under hot pressing and reduce the amount of glue overflow, while the small-scale viscous latex particles with a linear structure can improve the bonding strength of the adhesive. The waterborne polyurethane adhesive prepared in the present application has the advantages of small hot pressing deformation, small glue overflow, and high bonding strength. In addition, the waterborne polyurethane adhesive of the present invention can be precisely and patterned by printing, and is suitable for high temperature and high pressure composite construction processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The particle size distribution curves of the elastic component A in Synthesis Example 1 and the viscous component B in Synthesis Example 2 of this application;

[0069] Figure 2 This is the peel strength curve of the water-based adhesive of Example 1 and Example 2 of the present application. DETAILED DESCRIPTION

[0070] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0071] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0072] Polytetramethylene glycol and polyethylene adipate were purchased from Zhejiang Huafeng Synthetic Resin Co., Ltd. 2,2-Dihydroxymethylbutyric acid was purchased from Perstorp (Shanghai) Chemical Products Trading Co., Ltd. Toluene diisocyanate was purchased from Wanhua Chemical Group Co., Ltd. Triethylamine, diethylenetriamine, and hydroxyethylenediamine were purchased from Sinopharm Chemical Reagent Co., Ltd. Defoamers, leveling agents, and thickeners were from Digo Additives.

[0073] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0074] The test methods for the physical and mechanical properties of water-based adhesives are as follows:

[0075] The particle size and particle size distribution of the large-scale particle size elastic component A and the small-scale particle size viscous component B of the water-based adhesive are tested by Mastersizer 3000+ laser particle size analyzer.

[0076] Under high temperature and high pressure construction conditions, the test method for the overflow rate of water-based adhesives is as follows: Design a screen printing method to print a 0.4mm thick and 10mm wide strip on a fabric, and then cover it with another piece of fabric. Place the two pieces of fabric in a hot press machine and heat press at 125℃ for 90s, with a pressure of (0.1~1.5kg / cm 2). The width change of the test printed strip is the overflow rate of the water-based adhesive under high temperature and high pressure conditions; the calculation formula is as follows:

[0077] Glue overflow rate = (strip width after high temperature hot pressing - designed printing width) / designed printing width × 100%.

[0078] The peel strength test method of the water-based adhesive is as follows: the above-mentioned printed and hot-pressed fabric is cut into 10mm×200mm strips, and the fabric is peeled off in the 180° direction at a tensile speed of 50mm / min according to the Japanese JISK6854-2 "Test method for peel strength of adhesives" standard, which is the bonding strength (N / cm).

[0079] According to one embodiment of the present application, the preparation method of the elastic component A with large particle size includes the following steps:

[0080] (a) Polyol mixture melting and water removal: melt the mixed polyol at a suitable melting temperature and vacuum degree and remove the trace water inside;

[0081] (b) Dissolution and prepolymerization of the hydrophilic chain extender: After the operation of removing a small amount of water is completed, the vacuum is released under the protection of nitrogen, and the hydrophilic chain extender is added and stirred until dissolved, and then the polyisocyanate is added to obtain a prepolymer at a suitable prepolymerization temperature and prepolymerization time;

[0082] (c) Acetone dilution and inverse emulsification: The prepolymer is diluted with acetone to a suitable viscosity, and water is added for inverse emulsification. When the system temperature drops to the neutralization temperature, a neutralizing agent is added for neutralization;

[0083] (d) Polyamine chain extension and acetone extraction: The dripping rate of the polyamine chain extender is controlled, and the acetone is finally extracted by vacuum to obtain the elastic component A (aqueous polyurethane emulsion) with large particle size.

[0084] According to one embodiment of the present application, the preparation method of the small-scale particle size viscous component B comprises the following steps:

[0085] (e) Polyol mixing, melting and water removal: mixing and melting the polyols at a suitable temperature and vacuum degree and removing the trace water inside;

[0086] (f) Dissolution and prepolymerization of the hydrophilic chain extender: After the operation of removing trace moisture is completed, the vacuum is released under the protection of nitrogen, and the hydrophilic chain extender is added and stirred until dissolved, and then the polyisocyanate is added to obtain a prepolymer at a suitable prepolymerization temperature and prepolymerization time;

[0087] (g) Acetone dilution and inverse emulsification: The prepolymer is diluted with acetone to a suitable viscosity, and water is added for inverse emulsification. When the system temperature drops to the neutralization temperature, a neutralizing agent is added for neutralization;

[0088] (h) Diamine chain extension and acetone removal: The dropping rate of the diamine chain extender and the chain extension reaction temperature are controlled, and the acetone is finally vacuum-extracted to obtain a viscous component B (aqueous polyurethane emulsion) with a small particle size.

[0089] Synthesis Example 1 Preparation of elastic component A with large particle size

[0090] 4032 g of polytetrahydrofuran diol [Mn=2000] and 3024 g of polyethylene adipate [Mn=3000] were placed in a reaction kettle, fully melted at 100° C., and water was removed under a vacuum degree of -0.1 MPa.

[0091] The vacuum was released under nitrogen protection, 280 g of 2,2-dimethylolbutyric acid was added, and after it was completely dissolved, 1346 g of toluene diisocyanate was added, and the mixture was reacted at 75° C. for 2 hours to obtain a prepolymer.

[0092] 6400 g of acetone was added to the prepolymer to adjust its viscosity to 500 mPa*s, 8950 g of water was added, the temperature was lowered to 40° C., and 191 g of triethylamine was added to carry out a neutralization reaction.

[0093] 87.4 g of diethylenetriamine was dissolved in 500 g of water and added to the reaction system at a drop rate of 20 ml / min. The chain extension reaction was carried out at 40°C for 30 min, and the acetone in the system was extracted. The elastic component A with large particle size was obtained, and its particle size distribution is as shown in the attached figure. Figure 1 The particle size distribution range of the large-scale particle size elastic component A is: 0.1-1μm and 1-10μm.

[0094] Among them, the raw material composition ratio of the elastic component A with large particle size is calculated in weight percentage:

[0095] Polytetrahydrofuran diol [Mn = 2000]: 21.90%;

[0096] Polyethylene adipate [Mn = 3000]: 16.43%;

[0097] 2,2-dihydroxymethylbutyric acid: 1.52%;

[0098] Toluene diisocyanate: 7.31%;

[0099] Triethylamine: 1.04%;

[0100] Diethylenetriamine: 0.47%;

[0101] Water: 51.33%.

[0102] Synthesis Example 2 Preparation of small-scale particle size viscous component B

[0103] 4050 g of polytetrahydrofuran diol [Mn=2000] and 3050 g of polyethylene adipate [Mn=3000] were placed in a reaction kettle, fully melted at 100° C., and water was removed under a vacuum of -0.1 MPa.

[0104] The vacuum was released under nitrogen protection, 466 g of 2,2-dimethylolbutyric acid was added, and after it was completely dissolved, 1630 g of toluene diisocyanate was added, and the mixture was reacted at 75° C. for 2 hours to obtain a prepolymer.

[0105] 6400 g of acetone was added to the prepolymer to adjust its viscosity to 400 mPa*s, 9390 g of water was added, the temperature was lowered to 45° C., and 318 g of triethylamine was added to carry out a neutralization reaction.

[0106] 83.1 g of hydroxyethylenediamine was dissolved in 500 g of water and added to the reaction system at a drop rate of 10 ml / min. The chain extension reaction was carried out at 45°C for 30 min, and the acetone in the system was extracted. The small-scale particle size of the adhesive component B was obtained, and its particle size distribution is as shown in the attached figure. Figure 1 The particle size distribution range of the small-scale elastic component B is 0.1-1μm.

[0107] Among them, the raw material composition ratio of the small-scale particle size adhesive component B is calculated by weight percentage:

[0108] Polytetrahydrofuran diol [Mn = 2000]: 20.78%;

[0109] Polyethylene adipate [Mn = 3000]: 15.65%;

[0110] 2,2-dihydroxymethylbutyric acid: 2.39%;

[0111] Toluene diisocyanate: 8.36%;

[0112] Triethylamine: 1.63%;

[0113] Hydroxyethylenediamine: 0.43%;

[0114] Water: 50.76%.

[0115] Example 1 Water-based adhesive configuration

[0116] In terms of weight percentage, the water-based adhesive slurry ingredients are as follows:

[0117] The elastic component A with large particle size in Synthesis Example 1: 29%;

[0118] The small-sized viscous component B in Synthesis Example 2: 69%;

[0119] Other components C: defoamer 0.5%, leveling agent: 0.5%, thickener 1%.

[0120] According to the test method for the overflow rate of water-based adhesive under high temperature and high pressure construction conditions, the overflow rate of the water-based adhesive slurry of Example 1 was tested, and the results are shown in Table 1.

[0121] The peel strength test method of water-based adhesive was used to test the peel strength of the water-based adhesive of Example 1. The results are shown in Table 1. The peel strength curve is shown in Table 1. Figure 2 shown.

[0122] Example 2 Water-based adhesive configuration

[0123] In terms of weight percentage, the water-based adhesive slurry ingredients are as follows:

[0124] The elastic component A with large particle size in Synthesis Example 1: 49%;

[0125] The small-sized viscous component B in Synthesis Example 2: 49%;

[0126] Other components C: defoamer 0.5%, leveling agent: 0.5%, thickener 1%.

[0127] According to the test method for the overflow rate of water-based adhesive under high temperature and high pressure construction conditions, the overflow rate of the water-based adhesive slurry of Example 2 was tested, and the results are shown in Table 1.

[0128] The peel strength test method of water-based adhesive was used to test the peel strength of the water-based adhesive of Example 2. The results are shown in Table 1. The peel strength curve is shown in Table 1. Figure 2 shown.

[0129] Example 3 Water-based adhesive configuration

[0130] In terms of weight percentage, the water-based adhesive slurry ingredients are as follows:

[0131] The elastic component A with large particle size in Synthesis Example 1: 69%;

[0132] The small-size particle size of the viscous component B in Synthesis Example 2: 29%;

[0133] Other components C: defoamer 0.5%, leveling agent 0.5%, thickener 1%.

[0134] According to the test method for the overflow rate of water-based adhesive under high temperature and high pressure construction conditions, the overflow rate of the water-based adhesive slurry of Example 3 was tested, and the results are shown in Table 1.

[0135] The peel strength test method for water-based adhesives was used to test the peel strength of the water-based adhesive of Example 3. The results are shown in Table 1.

[0136] Comparative Example 1 Comparison of water-based adhesive configuration

[0137] In terms of weight percentage, the water-based adhesive slurry ingredients are as follows:

[0138] The elastic component A with large particle size in Synthesis Example 1: 98%;

[0139] Other components C: defoamer 0.5%, leveling agent: 0.5%, thickener 1%.

[0140] According to the test method for the overflow rate of water-based adhesive under high temperature and high pressure construction conditions, the overflow rate of the water-based adhesive slurry of Comparative Example 1 was tested, and the results are shown in Table 1.

[0141] The peel strength test method of water-based adhesive was used to test the peel strength of the water-based adhesive of Comparative Example 1. The results are shown in Table 1.

[0142] Comparative Example 2 Comparison of water-based adhesive configuration

[0143] In terms of weight percentage, the water-based adhesive slurry ingredients are as follows:

[0144] The small-sized viscous component B in Synthesis Example 2: 98%;

[0145] Other components C: defoamer 0.5%, leveling agent: 0.5%, thickener 1%.

[0146] According to the test method for the overflow rate of water-based adhesive under high temperature and high pressure construction conditions, the overflow rate of the water-based adhesive slurry of Comparative Example 2 was tested, and the results are shown in Table 1.

[0147] The peel strength test method of water-based adhesive was used to test the peel strength of the water-based adhesive of Comparative Example 2. The results are shown in Table 1.

[0148] Table 1 Water-based adhesive overflow rate and peel strength numerical table

[0149]

[0150] The overflow rate data in Table 1 show that the elastic component A can effectively reduce the overflow rate of the adhesive, that is, the deformation under hot pressing is small.

[0151] The results of Examples 1-3 and Comparative Example 1 in Table 1 show that small-scale viscous component B is helpful to improve the peel strength of the adhesive. However, the slurry in Comparative Example 2, which is mainly composed of viscous component B with small particle size, shows a lower peel strength. The reason is that the amount of glue overflowed from the viscous component B is large. After hot pressing, the adhesive is pressed and almost penetrates into the interior of the fabric. The amount of glue between the fabric interface layers is very small, so the peel strength is low. The fabric damage described in Table 1 refers to the behavior of sample damage occurring in the fabric itself during the peeling process, indicating that the bonding strength between the adhesive and the fabric is greater than the strength of the fabric itself. The interface damage refers to the destructive behavior between the adhesive and the fabric occurring at the fabric interface.

[0152] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A water-based adhesive, characterized in that: The components include: Elastic component A with large particle size; A sticky component B with small particle size; Other auxiliary components C.

2. The water-based adhesive according to claim 1, characterized in that: The particle size distribution range of the elastic component A is 0.01-100 μm; The particle size distribution range of the viscous component B is 0-1.0 μm.

3. The water-based adhesive according to claim 1, characterized in that: The components of the water-based adhesive include, by weight percentage: Large-scale particle size elastic component A10-88%; Small particle size sticky component B10-88%; Other auxiliary components C 0-2%.

4. The water-based adhesive according to claim 1, characterized in that: The elastic component A is made of raw materials including the following components in weight percentage: Preferably, the viscous component B is made of raw materials including the following component contents by weight percentage:

5. The water-based adhesive according to claim 4, characterized in that: The polyamine chain extender is selected from at least one of diethylenetriamine, triethylenetetramine and tetraethylenepentamine; Preferably, the diamine chain extender is selected from at least one of ethylenediamine, isophoronediamine, 1,6-hexanediamine, and β-hydroxyethylethylenediamine.

6. The water-based adhesive according to claim 1, characterized in that: The other auxiliary component C comprises a defoamer, a leveling agent and a thickener.

7. The method for preparing the water-based adhesive according to any one of claims 1 to 6, characterized in that: The steps include: S1, obtaining elastic component A with large particle size; S2, obtaining a viscous component B with a small particle size; S3, uniformly mixing the elastic component A, the viscous component B and the other auxiliary component C to obtain the water-based adhesive.

8. The preparation method according to claim 7, characterized in that: In step S1, the preparation process of the elastic component A includes the following steps: S1-1, melting the polyol and removing water under vacuum; S1-2, after step S1-1 is completed, release the vacuum in an inert atmosphere, add a hydrophilic chain extender and a polyisocyanate to the polyol in sequence, perform a prepolymerization reaction, and obtain a prepolymer; S1-3, adding acetone to the prepolymer to adjust the viscosity, then adding water for reverse emulsification, cooling to the neutralization temperature, adding a neutralizing agent for neutralization, and obtaining a neutralized mixed solution; S1-4, dropwise add the aqueous solution of polyamine chain extender into the neutralized mixed solution to carry out chain extension reaction, remove acetone in vacuo, and obtain elastic component A with large particle size.

9. The preparation method according to claim 7, characterized in that: In step S2, the preparation process of the viscous component B includes the following steps: S2-1, melting the polyol and removing water under vacuum; S2-2, after step S2-1 is completed, release the vacuum in an inert atmosphere, add a hydrophilic chain extender and a polyisocyanate to the polyol in sequence, perform a prepolymerization reaction, and obtain a prepolymer; S2-3, adding acetone to the prepolymer to adjust the viscosity, then adding water for reverse emulsification, cooling to the neutralization temperature, adding a neutralizing agent for neutralization, and obtaining a neutralized mixed solution; S2-4, dropwise add an aqueous solution of a diamine chain extender into the neutralized mixed solution to undergo a chain extension reaction, and remove the acetone in vacuo to obtain a viscous component B with a small particle size.

10. The preparation method according to claim 8 or 9, characterized in that: The dropping rate in step S2-1 and step S2-2 is independently selected from 10-100 ml / min; Preferably, the conditions for the chain extension reaction in step S2-1 and step S2-2 are independently selected from: reaction temperature of 25 to 50° C., and reaction time of 10 to 60 min.

Citation Information

Patent Citations

  • Hot-melt powder modified aqueous polyurethane resin and preparation method therefor

    CN110396290A

  • Polyurethane adhesive for seamless down jackets

    CN112143440A